Integration of Pancasila Student Profile Dimensions in Pancasila Education Textbook Class I Merdeka Curriculum - Putri, Elastika Amalia; Fajrin, Nilamsari Damayanti (eductum: Jurnal Literasi Pendidikan, 2025)
This research was conducted to provide an overview regarding the implementation of the Pancasila student profile in elementary level Pancasila education textbooks, which is an important foundation in forming the character of the nation's children. It is important to ensure that all dimensions of the Pancasila student profile that have been determined by the Ministry of Education and Culture in 2022 are covered comprehensively in textbooks. The absence of one of the dimensions of the Pancasila student profile in textbooks can cause unbalanced development in the understanding of the Pancasila student profile. The aim of this research is to provide an overview of the dimensions of the Pancasila student profile contained in the Pancasila Education class I textbook, merdeka curriculum with Erlangga publishers and to provide an overview of the distribution of the dimensions of the Pancasila student profile in each chapter in the Pancasila Education class I textbook, Merdeka curriculum with Erlangga publisher. The type of research used in this research is library research. The research approach used is a descriptive qualitative approach. The data collection technique used is documentation. The data analysis technique used is content analysis technique. The results of this research show that the Pancasila education textbook published by Erlangga contains all the dimensions of the Pancasila student profile and all the elements contained in the dimensions of the Pancasila student profile have been found. The distribution of the dimensions of the Pancasila student profile in each chapter is uneven.